A rapid α‐synuclein seed assay of Parkinson's disease CSF panel shows high diagnostic accuracy. Issue 2 (29th December 2020) - Orrù, Christina D.; Ma, Thong C.; Hughson, Andrew G.; Groveman, Bradley R.; Srivastava, Ankit; Galasko, Douglas; Angers, Rachel; Downey, Patrick; Crawford, Karen; Hutten, Samantha J.; Kang, Un Jung; Caughey, Byron
Abstract: Background: Assays that specifically measure α‐synuclein seeding activity in biological fluids could revolutionize the diagnosis of Parkinson's disease. Recent improvements in α‐synuclein real‐time quaking‐induced conversion assays of cerebrospinal fluid have dramatically reduced reaction times from 5‐13 days down to 1‐2 days. Objective: To test our improved assay against a panel of cerebrospinal fluid specimens from patients with Parkinson's disease and healthy controls from the MJ Fox Foundation/NINDS BioFIND collection. Methods: Specimens collected from healthy controls and patients with clinically typical moderate‐to‐advanced Parkinson's disease were tested without prior knowledge of disease status. Correlative analyses between assay parameters and clinical measures were performed by an independent investigator. Results: BioFIND samples gave positive signals in 105/108 (97%) Parkinson's disease cases versus 11/85 (13%) healthy controls. Receiver operating characteristic analyses of diagnosis of cases versus healthy controls gave areas under the curve of 95%. Beyond binary positive/negative determinations, only weak correlations were observed between various assay response parameters and Parkinson's disease clinical measures or other cerebrospinal fluid analytes. Of note, REM sleep behavioral disorder questionnaire scores correlated with the reaction times needed to reach 50% maximum fluorescence. Maximum fluorescence was inversely correlated with Unified Parkinson's Disease Rating Scale motor scores, which was driven by the patients without REM sleep behavioral disorder. Conclusions: Our improved α‐synuclein seed amplification assay dramatically reduces the time needed to diagnose Parkinson's disease while maintaining the high‐performance standards associated with previous α‐synuclein seed assays, supporting the clinical utility of this assay for Parkinson's disease diagnosis.